Trends and Determinants of Neonatal Mortality in Uganda: Analysis of the Uganda Demographic and Health Surveys - Asiime, John Bosco; Nyegenye, Wilson; Muyingo, Edmond (African Population Studies, 2020)
Uganda’s neonatal mortality has stagnated at 27 deaths per 1,000 live births over the past decade. Studying consistent factors could inform policy to reduce it. We used Uganda Demographic and Health Surveys (2001 to 2016) in analyses. Children who were not put on breast milk immediately after birth and children of mothers with multiple maternal risk factors were associated with higher odds (3.1 and 2.0 respectively) of neonatal deaths in 2016. The maternal risk factors include: young mothers, too old, short birth intervals or many children. Neonatal deaths was also higher among male compared to female newborns. There is a need to raise awareness about the importance of breastfeeding newborns immediately after birth. Interventions to reduce maternal risk factors are critical to reducing neonatal mortality in Uganda. Programmes need measures that can reduce more neonatal deaths among male than female.
Keywords: Neonatal; mortality; children; trends